Factors associated with prior testing for HIV, Syphilis, and Hepatitis B and C among transgender women and travestis in Brazil - Beo Oliveira Leite; Inês Dourado; Laio Magno; Sandro Sperandei; Carla Gianna Luppi; Maria Amelia de Sousa Mascena Veras (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To investigate the prior testing for HIV, syphilis, hepatitis B (HBV), and hepatitis C (HCV) among transgender women and travestis (TGW) in five Brazilian cities and identify factors associated with each of these previous tests. Methods: This is a cross-sectional study with the recruitment of TGW through respondent-driven sampling (TransOdara Study). The investigated outcome variable was prior testing for HIV, syphilis, HBV, and HCV in the last 12 months. The association between sociodemographic and behavioral factors with the outcome was analyzed using a binomial logistic regression with mixed effects. Adjusted odds ratios (aOR) and 95% confidence intervals (CI95%) were estimated. Results: The proportions of individuals with prior testing in the past year were as follows: 56.3% for HIV, 58.0% for syphilis, 42.1% for HBV, and 44.7% for HCV. Negative associations with prior testing were observed for individuals aged 35 years or older, whereas positive associations were found for those with high school education, those who experienced verbal or psychological violence in the last 12 months, and those who had commercial or casual partners in the last 6 months. Conclusion: There was low frequency of testing in the 12 months preceding the study for HIV, syphilis, HBV, and HCV compared to the guidelines established by the Ministry of Health. Expanding access to and engagement with healthcare and prevention services for TGW is an essential strategy in reducing the transmission chain of HIV and other sexually transmitted infections (STIs).